(untitled) (Research, Society and Development, 2023)
Overweight and obesity affected approximately 340 million children and adolescents in the world in 2016. In this sense, since obesity is a chronic disease, the factors related to this public health issue must be understood, including: sedentary lifestyle, low socioeconomic power and access to the health system. This study aimed to understand the main approaches to obesity prevention and management in primary health care. A narrative review of the literature was carried out, using the descriptors in the PubMed, SciELO and Periódico Capes databases, which obtained 342 articles, 31 of which were chosen for the basis of this review. According to the multifactorial etiology of obesity, recent studies have demonstrated the importance of therapeutic intervention in different spheres, through primary care, family support, school environment, technologies, pharmacological or surgical intervention. In addition, the difficulties encountered in carrying out the prevention and correct treatment of obesity in childhood are highlighted. Thus, multidisciplinary monitoring together with schools and the family is essential, promoting the health of young people and children, preventing obesity in adult life, as well as individual integrity and the comorbidities and diseases associated with the disease.